In Vitro Activity of Methanol Extract of Microalgae Hapalosiphon aureus Against Trichomonas vaginalis - Amal KH. Khalaf (University of Thi-Qar Journal of Science, 2020)
The present study targets the protozoan parasite Trichomonas vaginalis that causes a healthy problem among women and rarely among men, by the application of natural product or secondary metabolites extracted from the microalgae Hapalosiphon aureus for the first time in Iraq. methanol extract was explained high activity in three concentration recording 100% of parasite death at 200 µg\ml of methanol extract in about two days while 150 and 100 µg\ml of extract reports activity against the parasite after fourand fivedays post treatment respectively. GC- Mass spectrum of the methanol extract has explain presence of the compound (2- deca - 3,d- dienyloxy) carbonyl benzeoic acid in about 13.28 % from the total composition of methanol extract of microalgae.